2022
DOI: 10.37934/araset.28.2.2633
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study on the Effect of Miniaturized Impeller Diameter on Mechanical Performance in a Left Ventricular Assist Device

Abstract: Heart failure continues to be a major global health problem causing significant health issues and deaths. Left Ventricular Assist Device (LVAD) was developed as an alternative to heart transplant to support the patients with severe end stage heart failure. Despite the current advancement of LVAD, constant improvements are always being made in making it smaller LVADs tailored for patients with smaller physiology while still maintaining the flow ventricular pump capability to the body. This study evaluated the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(10 reference statements)
0
0
0
Order By: Relevance
“…It has been reported that the airflow can be improved by 14.5 times with the provision of a both-side opening interconnected corridor as compared to a single-sided classroom ventilation system. CFD (computational fluid dynamics) is a virtual tool that has been widely used to investigate the fluid flow behaviour with a greater accuracy level [15][16][17][18]. Bayoumi [19] investigated the ventilating effect through a hybrid ventilation system (Mechanical and buoyancy-driven flow) in a hot climate like Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the airflow can be improved by 14.5 times with the provision of a both-side opening interconnected corridor as compared to a single-sided classroom ventilation system. CFD (computational fluid dynamics) is a virtual tool that has been widely used to investigate the fluid flow behaviour with a greater accuracy level [15][16][17][18]. Bayoumi [19] investigated the ventilating effect through a hybrid ventilation system (Mechanical and buoyancy-driven flow) in a hot climate like Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%